2020
DOI: 10.1097/pcc.0000000000002472
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Peri-Intubation Cardiac Arrest in Pediatric Cardiac Intensive Care Patients: A Multicenter Study*

Abstract: Objectives: Endotracheal intubation is associated with hemodynamic adverse events, including cardiac arrest, especially in patients with cardiac disease. There are only a few studies that have evaluated the rate of and risk factors for endotracheal intubation hemodynamic complications in critically ill pediatric patients. Although some of these studies have assessed hemodynamic complications during intubation in pediatric cardiac patients, the frequency of and risk factors for peri-intubation cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…A retrospective analysis of 3 US pediatric ICUs from 2015 to 2017 found a 7% incidence of cardiac arrest in patients undergoing endotracheal intubation. 54…”
Section: Sudden Cardiac Arrest Ventricular Arrhythmias and Inherited ...mentioning
confidence: 99%
“…A retrospective analysis of 3 US pediatric ICUs from 2015 to 2017 found a 7% incidence of cardiac arrest in patients undergoing endotracheal intubation. 54…”
Section: Sudden Cardiac Arrest Ventricular Arrhythmias and Inherited ...mentioning
confidence: 99%
“…5,8 Hypoxemia and hypotension are particularly hazardous risks for cardiac arrest. [9][10][11][12][13] Unfortunately, data are lacking regarding the effect of physiologically difficult airways on FPS-AE in the emergency department (ED). This study explores the association of physiologically and anatomically difficult airways with FPS-AE.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 11 studies with 14,424 intubations were included in the final analyses. 2 7 8 9 11 12 13 14 15 16 17 The search strategy for these studies is outlined in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified hypotension, hypoxemia, lower pH, and systemic ventricular dysfunction, recent cardiorespiratory arrest, status asthmaticus, and the need for multiple intubation attempts to be associated with increased risk of peri-intubation risk of cardiorespiratory arrest. 7,8,12,14,15 Previous studies have identified the use of ketamine to be associated with decreased risk of peri-intubation cardiorespiratory arrest. 11 The transition from negative pressure to positive pressure ventilation is associated with a significant change in physiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation